Pengaruh Anggaran Bidang Pendidikan dan Anggaran Bidang Kesehatan dan Pertumbuhan Ekonomi terhadap Indeks Pembangunan Manusia di Indonesia - Susilawati, Susilawati; Syukri, Muhammad (Universitas Batanghari Jambi, 2025)
The human development index in Indonesia is influenced by the education budget, health budget, and economic growth, both collectively and individually. Secondary time series data from 2003–2023 are used in this study. The Central Bureau of Statistics (BPS) of Indonesia and related publications and books provide data. This study uses multiple linear regression analysis, R² coefficient, and hypothesis testing (F and T). This study found that the realization of the education budget, health, and economic growth simultaneously affect the human development index. The incomplete execution of the education budget does not affect the human development index. Indonesia's human development index is influenced by economic growth and the implementation of the health budget. This study found that Indonesia's human development index is 49.2% influenced by the education budget, health budget, and economic growth, while the remaining 50.8% is influenced by external variables not examined in this study.